Effects of different monochromatic light on growth performance and liver circadian rhythm of Yangzhou geese - Yingqing Xu; Yi Tang; Yiyi Cheng; Wen Yang; Jie Liu; Binbin Guo; Gang Luo; Huanxi Zhu (Poultry Science)
The objective of this study is to examine the impact of monochromatic light on the circadian rhythms of blood melatonin and insulin-like growth factor 1 (IGF-1) levels, liver clock genes, and melatonin receptors. A total of 144 male Yangzhou geese were randomly assigned to four groups based on light color, with each group consisting of 36 geese. The geese were provided with ad libitum access to food and water, and were raised for 70 days under a photoperiod of 16 hours of light and 8 hours of darkness. They were weighed every 10 days, and blood, liver, and pituitary gland samples were collected at six time points every four hours when the geese reached 70 days of age. The findings indicated that exposure to green light (GL) had a stimulating impact on weight gain in Yangzhou geese, while not significantly affecting the feed-to-weight ratio. After undergoing the four photochromic treatments, both plasma melatonin levels and liver positive feedback clock gene expression displayed a diurnal low-night high pattern, reaching their peak in the evening. Conversely, plasma IGF-1 and negative feedback clock genes exhibited an opposite trend. However, monochromatic light significantly down-regulated the gene expression, peak and amplitude of retinoic acid receptor-related orphan receptor α (RORα), as well as advancing or delaying the phase of the circadian rhythm. Among them, GL significantly up-regulated the gene expression of the melatonin receptors 1C (MEL1C); blue light (BL) significantly increased plasma melatonin concentration and IGF-1 concentration and significantly decreased the peak and amplitude of period 3 gene (PER3), resulting in almost no difference in the expression of PER3 at the six times; and red light (RL) significantly down-regulated the expression and the peak of MEL1C as well as the peaks and amplitudes of the seven liver clock genes, especially circadian locomotor output cycles kaput factor (CLOCK). Moreover, the peaks and amplitudes of the clock genes for BL and GL are almost identical, except for PER3. The findings of this study offer a theoretical framework for facilitating the development of meat geese and implementing a logical approach to managing lighting conditions.